2020
DOI: 10.1080/18117295.2020.1731647
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Teacher Talk Moves in Lessons on Basic Genetics Concepts in a Teacher Education Classroom

Abstract: Recent reforms in science education highlight the need for student-centred approaches to teaching in school curriculum policy in South Africa. Science teachers are required to move away from traditional teacher-centred practices which regard students as mere passive recipients of knowledge. In this study, we examine classroom talk for the type of student participation encouraging moves employed in lessons on basic genetics concepts and the related quality of instructional strategies employed by a university le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 19 publications
0
8
0
2
Order By: Relevance
“…It shows that the teacher tried to make the students establish a connection between previous knowledge and new concepts. A deep understanding of the content and associated concepts should be the goal of productive classroom interaction (Correnti et al, 2015; Morton, 2012) to build students' meaningful comprehension of knowledge (Buma & Nyamupangedengu, 2020). Accordingly, it was observed that with facilitating moves, the teacher aimed to support the students' knowledge construction and mathematics learning.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…It shows that the teacher tried to make the students establish a connection between previous knowledge and new concepts. A deep understanding of the content and associated concepts should be the goal of productive classroom interaction (Correnti et al, 2015; Morton, 2012) to build students' meaningful comprehension of knowledge (Buma & Nyamupangedengu, 2020). Accordingly, it was observed that with facilitating moves, the teacher aimed to support the students' knowledge construction and mathematics learning.…”
Section: Discussionmentioning
confidence: 99%
“…The dialogues that include eliciting moves reveal that the teacher evaluated students' prior knowledge before introducing a new mathematical concept through questioning related facts or procedures. According to Buma and Nyamupangedengu (2020), teachers should prompt students' responses to make a link between their prior knowledge and new concepts. Thus, it can be said that the teacher displays attempts for providing this essential connection in his lessons and tries to construct knowledge through teacher-student interactions in the classroom setting (Chin, 2006).…”
Section: Distribution Of Teacher Movesmentioning
confidence: 99%
See 3 more Smart Citations